2003
DOI: 10.1046/j.1471-4159.2003.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptor Nurr1 directly transactivates the promoter activity of the tyrosine hydroxylase gene in a cell‐specific manner

Abstract: Tyrosine hydroxylase (TH) catalyzes the first and rate-limiting step of catecholamine synthesis and its expression is necessary for neurotransmitter specification of all catecholaminergic neurons, while dopamine b-hydroxylase (DBH) is essential for the noradrenergic phenotype. In the present study, we show that Nurr1, an orphan nuclear receptor critical for dopaminergic (DA) neuron development, directly transactivates the promoter activity of the TH gene in a cell type-dependent manner, while it does not regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
141
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 45 publications
6
141
1
2
Order By: Relevance
“…3C). In vivo chromatin immunoprecipitation (ChIP) assay clearly showed that Nurr1 is recruited to both NL1 and NL3 sites of the TH promoter in AQ-and CQ-treated cells (20), suggesting that Nurr1 is directly involved in AQ-and CQmediated induction of TH gene expression (Fig. 3D).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…3C). In vivo chromatin immunoprecipitation (ChIP) assay clearly showed that Nurr1 is recruited to both NL1 and NL3 sites of the TH promoter in AQ-and CQ-treated cells (20), suggesting that Nurr1 is directly involved in AQ-and CQmediated induction of TH gene expression (Fig. 3D).…”
Section: Resultsmentioning
confidence: 98%
“…In our original assays using the reporter construct p4xNL3-Luc containing four copies of the NBRE-like NL3 motif residing in the TH promoter (20), AQ and CQ activated luciferase reporter activity up to approximately 3-fold in a dose-dependent manner ( Fig. 1B and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies focused mainly on the human (Kessler et al, 2003;Romano et al, 2005;Jin et al, 2006), mouse (Kim et al, 2003a) and rat models (Gandelman et al, 1990 et al, 2003b). In a previous report, a 13 kb DNA fragment containing the human TH promoter was isolated from a genomic DNA library, sequenced and utilized to generate both a transgenic animal model (Kessler et al, 2003) and a variety of recombinant minimal TH promoters assembled in a self-inactivating lentiviral vector system (Romano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Another striking difference between the human and murine models was observed in a more recent study on the nuclear orphan receptor NR4A2 (Nurr1), which did not affect human TH gene expression in hNPCs, in contrast to the mouse and rat systems (Jin et al, 2006). Nurr1 is required to transactivate mouse TH minimal promoters (Iwawaki et al, 2000;Kim et al, 2003a), as well as other unrelated promoters, such as the osteocalcin promoter in mouse osteoblasts (Pirih et al, 2004). However, TH gene expression did not depend on a direct Nurr1-mediated transactivation in the human model (Jin et al, 2006).…”
mentioning
confidence: 99%